2014
DOI: 10.1242/jeb.109025
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the role of the pharyngeal jaw apparatus in the sound-producing mechanism of Haemulon flavolineatum (Haemulidae)

Abstract: Grunts are fish that are well known to vocalize, but how they produce their grunting sounds has not been clearly identified. In addition to characterizing acoustic signals and hearing in the French grunt Haemulon flavolineatum, the present study investigates the soundproduction mechanism of this species by means of high-speed X-ray videos and scanning electron microscopy of the pharyngeal jaw apparatus. Vocalizations consist of a series of stridulatory sounds: grunts lasting ~47 ms with a mean period of 155 ms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Quantitative comparisons indicate the same sounds are produced during food processing as in distress situations. Videos showed cyclic movements during sound production were similar to movements employed in food processing, and electron microscopy revealed traces of erosion on different teeth of the pharyngeal jaws (Bertucci et al ., ).…”
Section: The Concept Of Exaptationmentioning
confidence: 97%
See 2 more Smart Citations
“…Quantitative comparisons indicate the same sounds are produced during food processing as in distress situations. Videos showed cyclic movements during sound production were similar to movements employed in food processing, and electron microscopy revealed traces of erosion on different teeth of the pharyngeal jaws (Bertucci et al ., ).…”
Section: The Concept Of Exaptationmentioning
confidence: 97%
“…Rubbing of upper and lower pharyngeal teeth produces stridulatory sounds (Burkenroad, 1930;Moulton, 1958). Bertucci et al (2014) performed a study on the French grunt (Haemulon flavolineatum, Haemulidae) using hydrophones to record sounds, high-speed X ray videos (to see bone movements inside the buccal cavity) and electron microscopy to study the teeth of the pharyngeal jaws was realized. Quantitative comparisons indicate the same sounds are produced during food processing as in distress situations.…”
Section: Haemulidae: Sound Production From Pharyngeal Jawsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, this work should be repeated with modern physiological and acoustic tools. A recent study using X-ray videos has conclusively demonstrated sound pulses generated by rubbing pharyngeal teeth in the French grunt Haemulon flavolineatum (Bertucci et al 2014).…”
Section: Stridulation Mechanismsmentioning
confidence: 99%
“…In some cases, a secondary swim bladder function has evolved that enables these species of fish to produce sound for acoustic communication (Fine & Parmentier, 2015;Kasumyan, 2008;Parmentier & Diogo, 2006). In grunts (Haemulidae) and clownfishes (Pomacentridae), the swim bladder acts as an acoustic amplifier to increase the sound level produced by the stridulation of hard skeletal parts including vibrations of the rib cage driven by jaw snapping (Bertucci, Ruppe, Van Wassenbergh, Compere, & Parmentier, 2014;Colleye, Nakamura, Fr ed erich, & Parmentier, 2012;Parmentier et al, 2007). In toadfishes and midshipman (Batrachoididae), sound is produced predominantly by reproductive males that have enlarged sonic muscles attached to their swim bladders and when contracted vibrate the bladder to yield high sound level acoustic signals for social communication (Bass & McKibben, 2003;Fine, Burns, & Harris, 1990;Fine, Bernard, & Harris, 1993;Fine, Malloy, King, Mitchell, & Cameron, 2001;Fine & Parmentier, 2015).…”
Section: Introductionmentioning
confidence: 99%